West European Perceptions of NATO. - United States. International Communication Agency. Office of Research and Evaluation. (Tufts University. Tisch Library., 2019)
An assessment of West European public opinion on issues relating to NATO's strength and credibility. Results are based on national public opinion surveys taken in Italy, Britain, Germany, France, Denmark and the Netherlands between March 1 and April 8, 1978.; Research Report M-7-78